Public engagement during a typhoid conjugate vaccine trial in Lalitpur, Nepal- experience, challenges and lessons learnt - Dahal, A; Shakya, M; Pant, D; Adhikari, A; Colin-Jones, R; Theiss-Nyland, K; Pollard, AJ; Basnyat, B; Shrestha, S (Taylor and Francis, 2022)
Typhoid is a public health problem in Nepal. To generate evidence on the impact of Typhoid Conjugate Vaccine (TCV), a phase 3, double-blind, randomized controlled trial was conducted in Lalitpur, Nepal. 20,000 children aged between 9 months and ≤16 years were vaccinated with a new TCV, or control vaccine. Participants were actively followed for safety and efficacy over 2 years through passive surveillance (PS) clinics. Several challenges were encountered during vaccination and PS stemming from misinformation, misconception, and fear around clinical trials in the community. Public engagement (PE) activities were conducted across various tiers moving from decision makers in the first tier; to elected local representatives in the second tier; ending with interaction in community with parents/guardians of the targeted population. Prior and during vaccination, engagement was conducted to inform about the study and discuss the importance of vaccination. Post-vaccination, engagement was conducted to inform about PS clinics, alleviate study concerns and share study updates. Direct and continuous interaction with community stakeholders, including parents/guardians of the targeted population contributed to build trust around the study and community willingness to be involved. It helped to raise awareness, drive away misconceptions, and allowed adaptation according to feedback from community members.